Exclusive Sharing & Virtualization of the Cellular Network - FORDE, TIM; DOYLE, LINDA; MACALUSO, IRENE (IEEE, 2011)
The focus of this paper is to progress a discussion about the redefinition of what it means to be a cellular network operator. Alternative modes of ownership may allow for the creation of more flexible cellular networking environments in which competition for packages of resources, i.e. the licenced spectrum, the RAN and core network, ensures that the most efficient architectures win out. This paper introduces the concept of the Cellular Network Cloud and Utility Cellular Networking as a means to explore the possibilities for such revolution in the way in which cellular networks are owned and operated. As a step towards evaluating the technical feasibility of such a paradigm, a flexible auction model that enables us to auction spectrum as a continuous good, as opposed to a collection of discrete items, is presented.
IEEE Symposium on New Frontiers in Dynamic Spectrum (DySPAN)
PUBLISHED
Aachen, Germany
Keywords: Networks; Smart & Sustainable Planet